Effect of Seedling Date and Plant Density on Growth and Yield of Local Red Onion Variety Allium cepa L - Albabilie, Rawaa M. M.; Alabdalla, Osama H.; Bathoush, Roula G.; Alozon, Mostafa M. (Al-Mukhtar Journal of Sciences, 2022)
The experiment was carried out in the General Commission for Agricultural Research, Syria. during the seasons 2019/2020 in order to investigate the effect of seedling date and plant density on the growth and yield of the local red onions variety and getting the bulbs directly without going through the stage of bulblets. Onion seeds were planted on 3 dates, with an interval of two weeks between dates (15/9, 30/9, 15/10). The seedlings were planted in the field on these dates (30/10, 15/11, 30/11) and with 3 plant densities (40, 20, 14 plant/m2). The results indicated that the first date had a significant difference in indicators (height of plants, number of leaves, bulb weight, onion diameter, productivity (68.69 cm, 7.89 leaf/plant, 199.3 g, 7.87 cm, 2130 kg/m2, respectively). As for the plant density, the plant density (14 plant/m2) had a significant difference to all studied indicators (69.15 cm, 7.66 leaf/plant, 238.1 g, 7.74 cm, 1667 kg/m2, respectively). As for the interaction there was a significant difference of the first planting date with third plant density, with the possibility of adopting this shared treatment in shortening the life cycle of onions of the local red variety.